Stealing the network how to own a continent - 131ah.; Russell, Ryan, 1969-; Moss, Jeff. (Rockland, Mass. : Syngress ; [Sebastopol, Calif.] : Distributed by O'Reilly & Associates in the United States and Canada, 2004)
This is a book that will create enormous debate within the technical and the counter-terrorism communities. While there will be the inevitable criticism that the material contained in the book could be used maliciously, the fact is that this knowledge is already in the hands of our enemies. This book is truly designed to inform while entertaining (and scaring) the reader, and it will instantly be in demand by readers of "Stealing the Network: How to Own the Box" * A meticulously detailed and technically accurate work of fiction that exposes the very real possibilities of such an event occurring * An informative and scary insight into the boundries of hacking and cyber-terrorism * Written by a team of the most accomplished cyber-security specialists in the world.
Written by today's leading security and counter-terriorism experts, this sequel to "Stealing the Network: How to Own the Box" operates on a truly global stage when the network infrastructure of an entire continent is compromised.
Control yourself / Ryan Russell -- The lagos creeper / 131ah -- Product of fate: the evolution of a hacker / Russ Rogers -- A real gullible genius / Jay Beale -- For whom Ma Bell tolls / Joe Grand -- Return on investment / Fyodor -- h3X and the big picture / FX -- The story of Dex / Paul Craig -- Automatic terror machine / Tim Mullen -- Get out quick / Ryan Russell.
"Foreword by Jeff Moss, President & CEO, Black hat, Inc"--Cover.
Keywords: Computer hackers -- Fiction; Computer security -- Fiction; Cyberterrorism -- Fiction; Short stories; Electronic books; Suspense fiction